The Comparative Study of the Therapeutic Effects and Mechanism of Baicalin, Baicalein, and Their Combination on Ulcerative Colitis Rat - Liang, Shuai; Deng, Xin; Lei, Lei; Zheng, Yao; Ai, Jiao; Chen, Linlin; Xiong, Hui; Mei, Zhinan; Cheng, Yung-Chi; Ren, Yongshen (Frontiers in Pharmacology, 2019)
Baicalin and baicalein are the primary effective substance of scutellaria baicalensis. It has been reported that baicalin and baicalein protect rats from ulcerative colitis(UC). Baicalin and baicalein have differential pharmacological of activities anti-inflammation, anti-oxidation, lipid-lowering and liver-protection in vivo and in vitro. It has been reported that UC has a great relationship with TH17/Treg regulation. The current study’s aims to determine the pharmacodynamic differences and potential mechanisms of baicalin, baicalein and their combinations[YSR(Young scutellaria baicalensis ratio of baicalin and baicalein=4:1), WSR(Withered scutellaria baicalensis ratio of baicalin and baicalein=1:1)] in the treatment of UC. We established UC model rats by composite factors [high-sugar and high-fat diet, high-temperature and high-humidity environment(HTHE) with Escherichia coli infection] to compare the therapeutic Effects and mechanisms of baicalin, baicalein and their combination, and then analyzed their metabolism in target tissue. As a result, the study shows that baicalin, baicalein, YSR, and WSR all have significantly therapeutic effects on UC, and have significantly different in the treatment of UC in the clinical symptoms and signs, such as fever, organ/body weight(BW) ratio, serum inflammatory cytokines levels, blood biochemistry and histopathology changes of main organs. We found that baicalin and baicalein have more potency in treating UC, and their combination provides a more comprehensive treatment, along with the higher of baicalin proportion, YSR generated the best effective treatment, which conforms to the traditional concept of optimization young Scutellaria baicalensis(Tiaoqin in Chinese) in treating large intestine disease. LC-MS/MS results show the conversion of baicalin and baicalein(in separation or combination) into six metabolites, baicalin, wogonoside, melaloside A, baicalein, Wogonin, and lamellar A e.g.. The levels of the six metabolites were significantly different in the large intestine, small intestine, and lung, but not in the serum. These results indicate that baicalin and baicalein should be used more accurately in specific diseases, especially baicalin or high content of baicalin in Scutellaria baicalensis should be preferred in treatment of UC.